Association of inherited variation in Toll-like receptor genes with malignant melanoma susceptibility and survival - Gast, Andreas; Lorenzo Bermejo, Justo; Claus, Rainer; Brandt, Andreas; Weires, Marianne; Weber, Alexander N. R.; Plass, Christoph; Sucker, Antje; Hemminki, Kari; Schadendorf, Dirk; Kumar, Rajiv (PLOS ONE, 2011)
The family of Toll-like receptors (TLRs) is critical in linking innate and acquired immunity. Polymorphisms in the genes encoding TLRs have been associated with autoimmune diseases and cancer. We investigated the genetic variation of TLR genes and its potential impact on melanoma susceptibility and patient survival. The study included 763 cutaneous melanoma cases recruited in Germany and 736 matched controls that were genotyped for 47 single nucleotide polymorphisms (SNPs) in 8 TLR genes. The relationship between genotype, disease status and survival was investigated taking into account patient and tumor characteristics, and melanoma treatment. Analysis of 7 SNPs in TLR2, 7 SNPs in TLR3 and 8 SNPs in TLR4 showed statistically significant differences in distribution of inferred haplotypes between cases and controls. No individual polymorphism was associated with disease susceptibility except for the observed tendency for TLR2-rs3804099 (odds ratio OR = 1.15, 95% CI 0.99-1.34, p = 0.07) and TLR4-rs2149356 (OR = 0.85, 95% CI 0.73-1.00, p = 0.06). Both polymorphisms were part of the haplotypes associated with risk modulation. An improved overall survival (Hazard ratio HR 0.53, 95% CI 0.32-0.88) and survival following metastasis (HR 0.55, 95% CI 0.34-0.91) were observed in carriers of the variant allele (D299G) of TLR4-rs4986790. In addition various TLR2, TLR4 and TLR5 haplotypes were associated with increased overall survival. Our results point to a novel association between TLR gene variants and haplotypes with melanoma survival. Our data suggest a role for the D299G polymorphism in the TLR4 gene in overall survival and a potential link with systemic treatment at stage IV of the disease. The polymorphic amino acid residue, located in the ectodomain of TLR4, can have functional consequences.
Gesehen am 08.08.2023